The Relationship Between Non-halal Animals And Pandemic Diseases According To The Shafie School Of Islamic Law - Mohamed Faiz Asyraf Razali; Ummu Hani Roslin; Amalina Ahmad Tajudin; Ahmad Syukran Baharuddin (RESEARCH CENTRE FOR SHARIA, FACULTY OF ISLAMIC STU, 2024)
Journal of Contemporary Islamic Law Volume 8 No.2 Page (53-60)